Citra Merek, Kepercayaan, dan Komitmen terhadap Loyalitas Pelanggan Aplikasi Transpportasi Online - Dendi Wijaya; Retno Endah Supeni; Yusron Rozzaid (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of brand image, trust, and commitment on customer loyalty of the Gojek online transportation application in Jember City. This research method is a comparative quantitative research. This research was conducted by distributing questionnaires to respondents who were used as samples in this study, Gojek online transportation users in Jember City. The sampling method in this research is purposive sampling. The analytical method used is the independent sample t-test. The results showed, based on the test results, namely, a) the results of the brand image test had a significant value of 0.005 <0.05 and T count 2.261 > T table 1.992; b) the results of the confidence test have a significant value of 0.005 <0.05 and T count 2.384 > T table 1.992; c) the results of the commitment test have a significant value of 0.005 <0.05 and T count 0.347 > T table 1.992. In conclusion, brand image, trust, commitment have a significant effect on customer loyalty. Keywords: Brand Image, Trust, Commitment, Loyalty, Test Independent Sample T-Test